Localizing wrapped M5-branes and gravitational blocks - Benetti Genolini, P; Gauntlett, J; Sparks, J (American Physical Society, 2023)
We consider $\mathcal{d}$ = 2, $\mathcal{N}$ = (0,2) SCFTs that can arise from M5-branes wrapping four-dimensional, complex, toric manifolds and orbifolds. We use equivariant localization to compute the off-shell central charge of the dual supergravity solutions, obtaining a result that can be written as a sum of gravitational blocks and precisely agrees with a field theory computation using anomaly polynomials and $\mathcal{c}$-extremization.